The review of the language position to the lyric style of Orfi Shirazi - Esmaeil Tajbakhash; Orang Ezadi (مطالعات زبانی و بلاغی)
“Orfi Shirazi” is a subtle and imaginative poet in the tenth century of hegira (963-999) who in despite of his short life has been become the propagation plotting of the new style to the Persian poem. This poet who has a sharp-sighted look and an over filled mind has been successful either to the new content creation or to the innovation of the new compositions and words. By this way, he forms his own creation of content in a creative language level with the special and innovative features. In this essay, some of the main features of language level of his poem have been studied with a stylistic look, by reviewing lyric of his poet and it's inflection and syntax has been analyzed. The results show that Orfi has come up with innovations in words and combinations by Morphological and syntactic features of Persian language. The research is based on library studies and descriptive-analytic method and orfi’s Qazals are used as a source of analysis.